Planificación colaborativa de la cadena de suministro del café arábigo para la empresa El Perezoso de la ciudad de Calceta - Flora Antonia, Intriago Alonzo (2019)
The research proposed was carried out at the “San Miguel de Sarampión” site, in Bolívar canton, province of Manabí. This work aimed to establish collaborative planning to improve the supply chain of El Perezoso coffee. For this purpose, information collection activities were carried out applying two questionnaires: for producers and commercial places and an interview with the manager of El Perezoso, and through a checklist information was obtained from all the actors. Another tool used for data collection was the observation tab. Once the necessary information was obtained, El Perezoso supply chain was characterized by a map containing four main links (suppliers, producers, shopping malls, consumers); then the responsibilities of each actor that are part of the chain were established. A SWOT matrix was proposed, and through the correlation of its variables (strengths, opportunities, weaknesses, threats), it was possible to obtain the vulnerability and profitability matrices with which actions could be taken to improve the supply chain. Through the application of the checklist, a general result was obtained for all the variables evaluated, which showed that the level of collaborative planning of El Perezoso is 1, which means that the type of strategy to be taken is the resources allocation. Finally, a basic plan was proposed to improve the positioning of the company and its supply chain.